POTENSI BAKTERI Bacillus spp. DALAM MENGHAMBAT Colletotrichum capsici PENYEBAB ANTRAKNOSA PADA CABAI MERAH SECARA IN VITRO - Sasiska Rani; Endang Triwahyu Prasetyawati; Herry Nirwanto (Plumula : Berkala Ilmiah Agroteknologi, 2022)
Colletotrichum capsici is an important pathogenic fungus that causes anthracnose in red chili. One of the efforts to resolve this problem is by using biological agents of Bacillus spp. bacteria. This study aims to determine the potential of five isolates of Bacillus spp. bacteria. there are Ba-6, Ba-9, Ba-12, Ba-15, and Ba-17 in inhibiting the pathogen C. capsici. Laboratory research was conducted using a Completely Randomized Design with 4 replications. In vitro testing was carried out using a dual culture technique on PDA media and a detach fruit test on chili. The results shows that the best inhibition effectiveness of C. capsici by in vitro testing of PDA media, namely Bacillus sp. Ba-9 isolate with 23.04% inhibition. Furthermore, in the detachment test, Bacillus sp. Ba-9 isolate was able to suppress the growth of C. capsici by 21.25% compared to control.